Evolution of l-1,2-Propanediol Catabolism in Escherichia coli by Recruitment of Enzymes for l-Fucose and l-Lactate Metabolism - Cocks, G. T. (1974)
A mutant strain of Escherichia coli capable of growth on l-1,2-propanediol was isolated previously. The mutant is characterized by constitutive production of a propanediol:nicotinamide adenenine dinucleotide (NAD) oxidoreductase which is essential for the new growth property. In the present study, it is shown that phage P1 cotransduces the genetic locus conferring this property and the genes for the utilization of l-fucose. A further indication of a relationship between these two growth properties is provided by the observation that wild-type E. coli excretes propanediol during fermentation of l-fucose. Under these conditions, a propanediol dehydrogenase (lactaldehyde reductase) is induced. This enzyme migrates on diethylaminoethyl-cellulose with the propanediol dehydrogenase produced constitutively by the mutant strain. A key event in the establishment of the ability to grow on propanediol is evidently a shift in the expression and function of propanediol dehydrogenase; an enzyme catalyzing formation of a reduced fermentation product anaerobically in wild-type cells functions aerobically to oxidize this same product in the mutant. l-Lactaldehyde, which is thus derived from propanediol, is converted to l-lactate by another dehydrogenase (l-lactaldehyde:NAD oxidoreductase) which is constitutively produced by both wild-type and mutant cells. The normal function of this enzyme is not yet established. l-Lactate is converted to pyruvate by an inducible NAD-independent l-lactate dehydrogenase. Thus, the carbons of propanediol are brought into the central metabolic network of the cell.